Do estado de necessidade no âmbito de condutas típicas praticadas por gestores de sociedades empresárias - Ayoub, Omar Ali (2022)
We aim to analyze the application of flagrant necessity on the actions involved in the management of corporations. To this end, we first address some aspects related to the risk society so that we can truly analyze the core of corporate activity and its complexity. From there we stipulate some methods for responsible corporate decisions, with the goal of demonstrating the existence of special cares and processes that must be adopted, as well as different management techniques that may aid the managers of corporations in decision making. After setting these premises, we aim, by studying the evolution of the concept of flagrant necessity, its history and its elements, to structure its application in the face of the many causes of risk (corporate crises), sorting them into three groups: factors that are completely independent of management, factors that are relatively independent of management, and factors that are entirely dependent on management. Finally, we study flagrant necessity in comparative law in order to systematically analyze its presence in the legal systems of other countries, most importantly in the Romano-Germanic system, common law, socialist laws, Muslim, Hindu and Jewish law, and in the Far East and African countries